PEMODELAN APLIKASI SISTEM PELAYANAN DOKTER PRAKTIK MENGGUNAKAN METODE PROTOTYPE Studi Kasus Klinik Dr. Lucya Agung (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
Dr. Lucya Agung’s clinic is a health service provider located in Cirebon City, West Java Province, where the information management system implemented is still done manually. To improve performance and ease in managing patient space data as well as making reports, an information system is proposed that can improve and facilitate services. The software development method used to build a doctor's practice information system is prototyping and modeling using UML (Unified Modeling Language). As well as software to support the development of this system using the PHP programming language, MySQL as database tools, and CodeIgniter framework. Medical practice information system in the clinic, Dr. Lucya Agung was built so that it can facilitate the processing of patient administration data, manage patient examination data,search patient data, and make reports.